Language death - Crystal, David (Cambridge University, 2013)
The rapid endangerment and death of many minority languages across the world is a matter of widespread concern, not only among linguists and anthropologists but among all concerned with issues of cultural identity in an increasingly globalized culture. A leading commentator and popular writer on language issues, David Crystal asks the fundamental question, 'Why is language death so important?', reviews the reasons for the current crisis and investigates what is being done to reduce its impact.